2021
DOI: 10.1038/s41591-021-01536-x
|View full text |Cite
|
Sign up to set email alerts
|

The SGLT2 inhibitor dapagliflozin in heart failure with preserved ejection fraction: a multicenter randomized trial

Abstract: Patients with heart failure and preserved ejection fraction (HFpEF) have a high burden of symptoms and functional limitations, and have a poor quality of life. By targeting cardiometabolic abmormalities, sodium glucose cotransporter 2 (SGLT2) inhibitors may improve these impairments. In this multicenter, randomized trial of patients with HFpEF (NCT03030235), we evaluated whether the SGLT2 inhibitor dapagliflozin improves the primary endpoint of Kansas City Cardiomyopathy Questionnaire Clinical Summary Score (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
309
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 388 publications
(358 citation statements)
references
References 35 publications
7
309
0
9
Order By: Relevance
“… 15 The EMPERIAL-Preserved trial (Empagliflozin Outcome Trial in Patients With Chronic Heart Failure With Preserved Ejection Fraction) did not show a significant effect of empagliflozin on KCCQ-TSS in a 12-week trial in ≈300 mildly symptomatic patients with HFpEF. 17 In contrast, the PRESERVED-HF trial (Dapagliflozin in Preserved Ejection Fraction Heart Failure) showed a significant improvement in the KCCQ-CSS with dapagliflozin in patients with HFpEF 16 ; the trial enrolled patients with obesity in the United States with >40% having New York Heart Association class III to IV symptoms.…”
Section: Discussionmentioning
confidence: 98%
“… 15 The EMPERIAL-Preserved trial (Empagliflozin Outcome Trial in Patients With Chronic Heart Failure With Preserved Ejection Fraction) did not show a significant effect of empagliflozin on KCCQ-TSS in a 12-week trial in ≈300 mildly symptomatic patients with HFpEF. 17 In contrast, the PRESERVED-HF trial (Dapagliflozin in Preserved Ejection Fraction Heart Failure) showed a significant improvement in the KCCQ-CSS with dapagliflozin in patients with HFpEF 16 ; the trial enrolled patients with obesity in the United States with >40% having New York Heart Association class III to IV symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…This obviously deviates from chronic treatments in large clinical trials, and it is therefore not known to which degree the direct and acute cardiac effects described in this review persist in the chronic condition. However, recently studies have reported that SGLT2i also improve outcome in the acute phase of heart failure in patients [ 86 ] and EMPA-Response trial [ 87 ], suggesting that also clinically SGLT2i have acute beneficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Techniques and stimuli used in clinical research to assess microvascular function in HFpEF; Table S2: Studies on peripheral microvascular function in HFpEF; Table S3: Studies on coronary microvascular function in HFpEF; Table S4: Intervention studies in HFpEF targeting the nitric oxide—protein kinase G pathway. References [ 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 ] are cited in the supplementary materials…”
mentioning
confidence: 99%